Ferulic Acid, an Angelica sinensis-Derived Polyphenol, Slows the Progression of Membranous Nephropathy in a Mouse Model. (11th July 2012) - Cheng, Chao-Wen; Chang, Wen-Liang; Chang, Li-Cheng; Wu, Chia-Chao; Lin, Yuh-Feng; Chen, Jin-Shuen
Abstract : Membranous nephropathy (MN) is a leading cause of adult nephrotic syndrome but lacks adequate treatment. Different extracts of Angelica sinensis (AS) and one of its active compounds, ferulic acid (FA), were used to evaluate the therapeutic effects in a MN mouse model. The MN model was grouped into three subgroups: no treatment (N-T), treatment at induction of MN (Pre-T), and treatment after full-blown MN (Post-T). The results showed that the methanol (ME) layer of AS extract exhibited a therapeutic effect on MN-induced proteinuria. The ME layer-enriched compound, FA, improved the hypoalbuminemia, hyperlipidemia, and proteinuria in both Pre-T and Post-T groups. Ferulic acid also reduced the formation of oxidative protein products and increased the synthesis of antioxidant enzymes in groups Pre-T and Post-T. Regarding angiogenesis factors, the antiangiogenic factors in renal glomeruli were increased in group N-T, but, after FA treatment, only one of the antiangiogenic factors, thrombospondin-1, showed a significant decrease. Furthermore, the expression of Th2 predominant showed significant decrease in both Pre-T and Post-T groups when compared to that of N-T group. In summary, FA retarded the progression of MN, and the mechanisms involved the regulation of oxidative stresses, angiogenic and antiangiogenic factors, and attenuation of Th2 response. Corrigendum to "Ferulic Acid, an Angelica sinensis-Derived Polyphenol, Slows the Progression of Membranous Nephropathy in a Mouse Model" dx.doi.org/10.1155/2016/7315875